2022
DOI: 10.5114/kitp.2022.122092
|View full text |Cite
|
Sign up to set email alerts
|

Primary aortoenteric fistula: is endovascular repair the prime option? A review of the literature

Abstract: Primary aortoenteric fistula (PAEF) is a rare entity that demands high clinical suspicion and efficient management in a limited time. The evolution of interventional radiology established endovascular repair (EVAR) as an attractive option. The English literature was searched using the PubMed database with the terms "primary aortoenteric fistula", "primary aortoduodenal fistula" or "aortoduodenal fistula", and "endovascular repair" in different combinations. Studies and original articles that described the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Less frequently reported symptoms included syncope, abdominal pain, and fever. The predominant pattern of symptoms observed was upper GI hemorrhage accompanied by hemodynamic instability [ 3 ], similar to the clinical presentation that observed in our patient.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Less frequently reported symptoms included syncope, abdominal pain, and fever. The predominant pattern of symptoms observed was upper GI hemorrhage accompanied by hemodynamic instability [ 3 ], similar to the clinical presentation that observed in our patient.…”
Section: Discussionsupporting
confidence: 85%
“…Primary aortoenteric fistulas (PAEF) most commonly affect the third part of the duodenum and the celiac aorta, with an incidence rate of 83 % [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This integrated approach aims to prevent aneurysm enlargement, reduce the risk of rupture, and intervene prior to the development of dissection or rupture. In addition to the common complications of rupture and bleeding, TAA can also lead to uncommon intestinal fistulas, where aortic inflammation and direct friction collaborate to spontaneously form primary fistulas [ 28 , 29 ]. The infiltration of immune cells could potentially explain the structural changes in blood vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…AEFs are defined as abnormal linkage between the lumen of the aorta and that of the gastrointestinal (GI) tract with an incidence rate of 0.1 % to 0.08 % [ 2 ]. Fistulization can occur either primarily, when no prior intervention has been performed on the aorta, or secondarily, developing after both open and endovascular aortic reconstruction even through a thrombosed graft [ 3 , 4 ]. The primary type is even rarer, with an incidence rate ranging between 0.04 % and 0.07 %, as indicated by autopsy studies, while the secondary type has a higher incidence rate, reported to be approximately or below 1 %.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology involves mechanical thinning of the aorta and outermost intestine due to repeated rubbing during each pulsation and GI peristalsis, leading to erosion and linkage between the two lumens. Less common causes of PAEFs include metastatic tumors, radiation therapy, foreign body ingestion, tuberculosis, and infections such as appendicitis or diverticulitis [ 3 , 7 ]. The most common communication is the celiac aorta and the duodenum, especially the third portion at a rate of 83 %.…”
Section: Introductionmentioning
confidence: 99%